The definitive guide to blockchain for accounting and business : understanding the revolutionary technology - Dutta, Saurav K. (Emerald Publishing Limited, 2020)
Blockchain: a disruptive technology, or a new chance for the business world? The answer is both. With potential to change how economic transactions are recorded, stored, and verified, blockchain is changing the very face of the accounting industry. Despite its ramifications, business students of today and the practicing accountants of tomorrow are not being adequately trained in this new technology, due to a lack of resources exploring it from an accountant and business expert's perspective. Through its discussion of real-world and 'use-cases' The Definitive Guide to Blockchain for Business and Accounting distils an abstract technology into relatable experiences for business professionals. Including chapters from practicing professionals in the blockchain industry, The Definitive Guide shows readers how this innovative technology is changing the fundamentals of the business world. With international subject matter experts, this exciting new book includes perspectives from accountants, auditors, CEOs and CTOs on how blockchain is rewriting the future of the business and accounting world.